Synthesis, in vitro evaluation, and radiolabeling of fluorinated puromycin analogues: potential candidates for PET imaging of protein synthesis - Betts, Helen M.; Sephton, Selena Milicevic; Tong, Carmen; Awais, Ramla; Hill, Philip J.; Perkins, A.C.; Aigbirhio, Franklin I. (American Chemical Society, 2016)
There is currently no ideal radiotracer for imaging protein synthesis rate (PSR) by positron emission tomography (PET). Existing fluorine-18 labelled amino acid-based radiotracers predominantly visualize amino acid transporter processes, and in many cases they are not incorporated into nascent proteins at all. Others are radiolabelled with the short half-life positron emitter carbon-11 which is rather impractical for many PET centers. Based on the puromycin (6) structural manifold, a series of 10 novel derivatives of 6 was prepared via Williamson ether synthesis from a common intermediate. A bioluminescence assay was employed to study their inhibitory action on protein synthesis which identified fluoroethyl analogue (7b) as a lead compound. The fluorine-18 analogue was prepared via nucleophilic substitution of the corresponding tosylate precursor in modest radiochemical yield 2±0.6% and excellent radiochemical purity (>99%) and showed complete stability over 3 h at ambient temperature.